Assessing health-related quality of life using EQ-5D-5L in adolescents with perpetuation of obesity - M Suganya; S Maragatham; D Padmapriya (Journal of Family Medicine and Primary Care)
Background: Obesity in adolescents is a global health issue with increasing prevalence in middle-income countries. This study aims to analyze the Health-Related Quality of Life of Adolescents with Obesity. Methods: A cross-sectional study was conducted in a tertiary care hospital. The adolescents were selected based on inclusion and exclusion criteria. In total, 62 adolescent patients with perpetuation of obesity were identified and interviewed. Agreed adolescents were given General information questionnaires and EQ-5D-5L. ANOVA was calculated using SPSS Version 21. Results: More than half of adolescents (67.8%) were in the weight status of Obesity-I. The variables of Weight status, Physical activity, Duration of obesity, and Number of comorbidities were strongly correlated with health-related quality of life of adolescent patients since the P value of EQ-5D-5L and EQ-VAS were <0.05 level. Conclusion: When compared to adolescents with obesity II and I status, adolescents with obesity III status had a lower health-related quality of life.